Review of the genus Karnyothrips (Thysanoptera, Phlaeothripidae) from Asia between India and Japan - Okajima, Shûji; Masumoto, Masami (Zootaxa, 2025)
The genus Karnyothrips, classified into the tribe Haplothripini of the subfamily Phlaeothripinae, is studied taxonomically from Asia. Forty-four species are recognized, of which 26 species are newly described, and two species are transferred from Apterygothrips and Xylaplothrips: K. acer Okajima, K. acutus sp. n., K. affinis sp. n., K. alpha Pitkin, K. antennalis Okajima, K. apoensis sp. n., K. breviceps sp. n., K. brevipilosus sp. n., K. capitatus sp. n., K. cyathomorphus Wang, Mirab-balou & Tong, K. expandosus Reyes, K. flavescens sp. n., K. flavicornis Okajima, K. flavipes (Jones), K. formosanus sp. n., K. infectus sp. n., K. inflatus Okajima, K. inpallens sp. n., K. insignis Okajima, K. lalae sp. n., K. longicaudus sp. n., K. macrommatus sp. n., K. maculatus sp. n., K. melaleucus (Bagnall), K. micans (Ananthakrishnan & Jagadish) comb. n. (transferred from Xylaplothrips), K. micrommatus sp. n., K. mucidus (Ananthakrishnan & Jagadish), K. nigriflavus Ramakrishna, K. oppositus sp. n., K. pacificus Okajima, K. pellucidus (Ananthakrishnan) comb. n. (transferred from Apterygothrips), K. pitkini sp. n., K. quadriconus sp. n., K. robustus Okajima, K. semiflavus sp. n., K. similis sp. n., K. simpliceps sp. n., K. spinulus Okajima, K. submaculatus sp. n., K. tenax sp. n., K. triconus sp. n., K. variabilis sp. n., K. vietnamensis sp. n. and K. yoshi Okajima. Two species, K. fungulus Ananthakrishnan and Xylaplothrips palmerae Chen, are synonymized with K. flavipes. One species is excluded from Karnyothrips: K. ateuchis Reyes from the Philippines is transferred to Reyesothrips gen. n. The generic definition and relationships of Karnyothrips are considered. An illustrated key for discriminating 43 Karnyothrips species from Asia is provided.